(untitled) (American International Journal of Cancer Studies, 2021)
Cancer is a lethal disease and a strong barrier to a better life expectancy. It is the first or second leading cause of death before the age of 70 years in 112 of 183 countries. Its incidence and mortality continue to grow rapidly all over the world. This manuscript is divided into four parts. Part I discusses obesity while Part II discusses the relationship between obesity and cancer. Part III and Part IV review the association of obesity on fifteen common cancers.